(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article scientifically substantiates the issues of education in the development of New Uzbekistan. As a result of large-scale reforms and creative work carried out in our country, the way of thinking and worldview of our people is changing. In our country, the importance of the life-giving idea «From national revival to national upsurge» in the development of the rule of law and civil society is growing.